Preconception health behaviors among women with planned pregnancies - Nascimento,Natália de Castro (2019)
ABSTRACT Objective: To identify determinants of preconception preparation among women with planned pregnancies. Method: A cross-sectional study with a probabilistic sample of 264 women between 18 and 49 years of age who had or were undergoing planned pregnancies, and were users of two School Health Centers in the city of São Paulo. Analysis was conducted through univariate and multiple logistic regression of three variable blocks: 1) social and demographic characteristics; 2) sexual and reproductive characteristics; 3) preexisting health conditions. Results: Women with higher education, belonging to economic groups A and B, and older women with infertility were more likely to perform preconception training. Conclusion: Preconception care has a strong social determination, as women with more favorable social profiles are more likely to perform it. Experience with infertility is also instrumental in the likelihood of preconception care.